PENGELOLAAN MODAL KERJA DALAM USAHA MENJAGA LIKUIDITAS DAN MENINGKATKAN PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Semen yang Terdaftar di Bursa Efek Indonesia Tahun 2012 - 2015) - Alimin, Zaenal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Cement companies are included in manufacturing companies in the sector of basic and chemical industry. This sub sector is categorized into strategic industry. The objective of this research is to identify and analyze the management of working capital, liquidity level, and profitability level of cement companies listed in the Indonesia Stock Exchange in the period of 2012 - 2015.This descriptive research uses secondary data in forms of financial statements. The analysis was performed on net working capital, working capital turnover, cash turnover, receivable turnover, inventory turnover, current ratio, quick ratio, cash ratio, return on assets, return on equity, and profit margin on sales.The results of this study show that the net working capital of the companies tends to increase during the year of 2012-2015 due to the their success in increasing sales. In addition, working capital turnover has generated good cash to ensure the companies’ activities in the next period. Furthermore, they have been in liquid state and able to generate profit.Keywords: Net Working Capital, Working Capital Turnover, Liquidity, Profitability